Maṇḍana-granthāvalī - Devendra (Sāhitya Saṅgama, 1992)
Complete works of a medieval Hindi poet; with study on his life and works by the editor
Poems. - Originally presented as the editor's thesis (Ph.D. – Banaras Hindu University, 1980) under the title: Hindī-rītikavitā ke pariprekshya meṃ kavi Maṇḍana kā adhyayana. - Includes index. - Includes bibliographical references. - Hindi in Devanagari-Schr
Keywords: Hochschulschrift; Maṇḍana 17th cent; Hindi poetry